2011
DOI: 10.1590/s1809-48722011000300016
|View full text |Cite
|
Sign up to set email alerts
|

Resultados a longo prazo com o uso do implante coclear em crianças: revisão sistemática

Abstract: Introduction: Cochlear Implant (CI) benefits given to children in the first years of usage have been thoroughly described in literature. Nonetheless, studies reporting the results after the device has been long used are scarce. Objective: Review the available evidence in literature to answer the query: "Did Cochlear Implant effectively contribute to develop the communication abilities in children and young adults who grew up with this device?Method: To answer the suggested query, a systematic literature review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 27 publications
0
11
0
3
Order By: Relevance
“…As observed in Figures 1 and 2, for both abilities, some children presented deviant results. Evidence in the literature has shown that the variability of the results can be associated with innumerable factors (4,28) and, although the research presents rigid exclusion criteria for variables that could negatively influence the benefit obtained with a CI, the variability of responses is observed.…”
Section: Discussionmentioning
confidence: 99%
“…As observed in Figures 1 and 2, for both abilities, some children presented deviant results. Evidence in the literature has shown that the variability of the results can be associated with innumerable factors (4,28) and, although the research presents rigid exclusion criteria for variables that could negatively influence the benefit obtained with a CI, the variability of responses is observed.…”
Section: Discussionmentioning
confidence: 99%
“…In the present review, 26 articles were found 2,6-30 , being eighteen analytical observational transversal studies 2,[6][7][8][9][12][13][14][17][18][19][20][21]23,24,[27][28][29] , four analytical observational longitudinal studies 10,11,16,22 , two reported case 15,25 , one experimental study 26 and one literature review 30 , consisting of nineteen national and seven international researches. The articles were separated in thematic bases and distributed in frames to results presentation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Taking into account the classification of scientific evidence levels (9)(10)(11) -according to the methodology of different types of research -articles consisting of case studies (evidence level 5), expert opinion (evidence level 6), abstracts from conference proceedings, theses and dissertations were excluded.…”
Section: Selection Criteriamentioning
confidence: 99%